PELATIHAN PEMBUATAN TABIR SURYA ANTI-UV PELINDUNG KULIT BERBASIS ALGAE COKLAT KEPADA PEMBUDIDAYA RUMPUT LAUT DI TELUK EKAS PADA MASA PANDEMI COVID-19 [TRAINING OF BROWN ALGAE ANTI-UV SUNSCREEN PROCESSING TECHNIQUE FOR SEAWEED FARMERS IN EKAS BAY DURING COVID-19 PANDEMIC] - Anggit L. Sunarwidhi; Ni Wayan Riyani Martyasari; Eka Sunarwidhi Prasedya; Sri Widyastuti; Haji Sunarpi (Universitas Pelita Harapan, 2021)
Exposure to ultraviolet (UV) light provides high effectiveness in inhibiting germs, bacteria and the Sars-Cov 2 virus that causes Corona Virus Disease-19 (COVID-19). However, due to the depletion of the ozone layer which acts to ward off short wave radiation, there is an increase of UV light radiation amount that reaches the earth's surface. As a result, human skin is exposed to UV radiation which can cause premature skin aging and even skin cancer. Researchers claim that brown algae contain anti-UV compounds that can absorb UV radiation. Therefore, it has been developed a skin protection cream based on brown algae seaweed that can protect human skin from exposure to UV radiation. This article reports on the introduction and training of how to produce anti-UV sunscreen for seaweed farmers who faces high intensity sun exposure on a daily basis. Participants were 20 person (wives and children of the farmers). In this training, video tutorial of making cream was played following with demonstration of making cream by the participants. After the training, it is hoped that the farmers wives and children will be able to produce this anti-UV sunscreen that was not for self-used to protection against UV radiation exposure, but could also for sale to increase the income of coastal communities during the COVID-19 pandemic. BAHASA INDONESIA ABSTRACT: Paparan sinar ultraviolet (UV) memberikan efektivitas yang tinggi dalam penghambatan kuman, bakteri hingga virus Sars-Cov 2 penyebab Corona Virus Disease-19 (COVID-19). Namun karena menipisnya lapisan ozon yang berperan menangkal radiasi gelombang pendek, maka radiasi akibat sinar UV sampai ke permukaan bumi. Akibatnya, kulit manusia terpapar radiasi UV yang dapat menyebabkan penuaan kulit secara dini dan bahkan kanker kulit. Para peneliti menyatakan bahwa algae coklat mengandung senyawa anti-UV yang dapat menyerap radiasi ultra violet. Karena itu, telah dikembangkan krim pelindung kulit berbasis rumput laut alga coklat yang dapat melindungi kulit manusia dari paparan radiasi UV. Artikel ini melaporkan pengenalan dan pelatihan cara pembuatan krim anti-UV kepada pembudidaya rumput laut yang sehari-hari harus berhadapan dengan terpaan matahari berintensitas tinggi. Hadir sejumlah 20 orang (para istri dan anak-anak pembudi daya). Dalam pelatihan ini diputarkan video tutorial membuat krim yang kemudian diikuti dengan demonstrasi membuat krim. Setelah pelatihan, diharapkan para istri dan anak pembudidaya dapat memproduksi krim anti-UV yang tidak saja dapat digunakan sendiri sebagai perlindung terhadap paparan radiasi UV, melainkan juga dapat dijual untuk meningkatkan pendapatan masyarakat pesisir pada masa pandemi COVID-19.